PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT KIMIA FARMA Tbk. - Yulia, Hana; Sulaeman, Sulaeman; H Suwiryo, Darmo (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
Promotion is one of the variables of the marketing mix is very important that the company implemented in marketing their products. Without the existence of promotional products received less attention from consumers. Target promotion can be achieved if the company allocates adequate promotional costs and with the cost of the promotion is expected to help the company achieve higher sales volumes. The purpose of this study was to determine the effect of promotion cost on the sales volume. Samples taken in this study was obtained from the financial statements PT.Kimia Farma Tbk. This study used a simple linear regression analysis method, t-test with 5% significance. The results of the analysis has been known that the cost of promotional effect on sales volume partially.